Direct hydrolysis and analysis of glycosidically bound aroma compounds in grapes and wines: comparison of hydrolysis conditions and sample preparation methods. (15th August 2014) - Hampel, D.; Robinson, A.L.; Johnson, A.J.; Ebeler, S.E.
Abstract Background and Aims Many aroma compounds occur as glycosidically bound precursors that do not contribute to fruit/beverage aroma until aglycone release during processing or storage. Existing procedures typically measure glycosidically bound compounds after first isolating the glyocoside fraction. The objectives of this work were to evaluate and develop rapid procedures for measuring glycosidically bound volatiles using direct acid or enzyme hydrolysis of fruit tissues or wine followed by analysis of the free volatiles by headspace solid‐phase microextraction coupled with gas chromatography mass spectrometry. Methods and Results Using a mixture containing free (linalool, ethyl decanoate, β‐ionone) and glycosidically bound standards (n‐octyl‐, n‐dodecyl‐, phenyl‐β‐D‐glucopyranoside), acid hydrolysis released 20–60% of the bound volatiles; significant degradation (>50%) of free volatiles occurred. Enzyme hydrolysis efficiently released glycosidically bound compounds (90–100%) while minimising artefactual changes of the free volatiles and further rearrangements of the aglycones. We also compared direct enzyme hydrolysis with hydrolysis of a glycoside fraction obtained by solid‐phase extraction (SPE). Different SPE columns were not equally effective at retaining glycosides; no column type was effective for all glycosides. Conclusions Direct hydrolysis of grape and wine samples (and comparison of volatiles before and after hydrolysis) is a useful approach for measuring 'aroma potential' compared with prior SPE isolation of the glycosides. Significance of the Study The method described here provides a rapid tool for characterising changes in glycosidically bound volatiles before and after processing (e.g. winemaking) and as a result of varying fruit maturity and/or other agricultural practices.